تأثير أبي علي الفارسي وابن جني في شافية ابن الحاجب -دراسة صرفية- - مصطفى, أ.م.د.دانا أحمد; كريم, أ.م.د.زانا شاباز (Sulaimani Journal for Humanities, 2023)
this research ( The Influence of Each Abi-Ali Al-farsi and Ibn-Jana on Ibn-Al-hajib in sharh Al-Shafia book) is an attempt to understand and looking deeper into those morphological aspects by which Ibn-Hajib was affected, in the works of both linguists before him, What makes the research more interesting is that we also shed lights on those topics in which Ibn-Al-hajib contradicted the two linguists, and answered them, another significance of this research is that he discussed the subjects according to the new morphological rules and data. The research generally contains of two chapters, the first one deals with the life and the works of Ibn-Al-Hajib briefly, while the second one throws light on the affects of the works of the two linguists before him on Ibn-Al-Hajib in (Sharh AL-shafiah) book, finally the most significant results are shown.